RURAL EDUCATION AND PEASANT RESISTANCE: THE EMANCIPATORY, DIALOGICAL AND ALTERNATING PEDAGOGICAL PRAXIS OF THE ROSALVO DA ROCHA RODRIGUES AGRICULTURAL FAMILY SCHOOL (EFAR) - Assuncao, Adenilso dos Santos; Camacho, Rodrigo Simao [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2023)
We present a reflection on the practice of Pedagogy in Alternating Cycle developed at Rosalvo da Rocha Rodrigues Agricultural Family School (EFAR). As pedagogical praxis in Rural Education, has links with Freirean Popular Education by opposing the capitalist of education project, by fomenting peasants in agricultural technicians who contribute to the emancipation of excluded and subordinated subjects through the organization and strengthening of class identity for the sociopolitical processes of territorial resistance.This article analyzes the political/school experience through the dialectical method, starting from the concrete history of the struggle for the conquest of the land. The methodologies used were theoretical discussion a and field research of EFAR, where we interviewed educators, students and managers.
Keywords: Peasantry; Field Education; Popular Education; Alternating Education; Agricultural Family School